2019
DOI: 10.3390/fib7110095
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hybridisation on the Low Velocity Falling Weight Impact and Flexural Properties of Flax-Carbon/Epoxy Hybrid Composites

Abstract: The trend of research and adoption of natural plant-based fibre reinforced composites is increasing, with traditional synthetic fibres such as carbon and glass experiencing restrictions placed on their manufacture and use by legislative bodies due to their environmental impact through the entire product life cycle. Finding suitable alternatives to lightweight and high-performance synthetic composites will be of benefit to the automotive, marine and aerospace industries. This paper investigates the low-velocity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 11 publications
2
18
0
Order By: Relevance
“…Flax fibers are approximately 70 to 75% cellulose, and range in diameter from 12 to 16 μm, with lengths up to 90 cm [ 15 ]. Flax fibers have undergone testing as hybrid reinforcing materials for composite materials [ 16 ].…”
Section: Characteristics Of Fibersmentioning
confidence: 99%
“…Flax fibers are approximately 70 to 75% cellulose, and range in diameter from 12 to 16 μm, with lengths up to 90 cm [ 15 ]. Flax fibers have undergone testing as hybrid reinforcing materials for composite materials [ 16 ].…”
Section: Characteristics Of Fibersmentioning
confidence: 99%
“…In this regard, hybridisation of plies of plant and synthetic fibres represents a significant strategy to reduce weight and carbon footprint of traditional composite materials, while retaining a sufficient mechanical performance to permit structural applications. In particular, it has been shown that hybrid composite materials can improve impact and bending resistance in comparison with non-hybrid ones [4][5][6][7]. According to Dong [8], hybrid composites including plant fibres were fabricated most frequently with glass fibres.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4 displays scanning electron microscopy (SEM) pictures of broken surfaces following the impact of plain flax/epoxy composites, which reveal significant fibre breakage and disorder, with one big group of fibres serving as an initial focal point. The following magnification scales (150 and 300) revealed matrix cracking and epoxy debonding from individual fibres, as well as fibre bending and debonding around a kink band in the flax fibre structure, with evident twisted and flattened fibres [ 167 ]. This was similar to the failure modes done by Dhakal et al, as in Figure 5 .…”
Section: Failure Mode Of Perforation Resistance On Hybrid Compositesmentioning
confidence: 99%